12. WHAT TO DO WHEN THERE IS NO EUPLOID EMBRYOS? TRANSFER MOSAIC EMBRYOS OR PROPOSE ANOTHER PGT-A CYCLE?. (August 2019) - Cetinkaya, M.; Pirkevi Cetinkaya, C.; Tufekci, M.A.; Cinar Yapan, C.; Kumtepe Colakoglu, Y.; Yelke, H.; Kahraman, S.
Abstract : Introduction: Embryonic mosaicism is defined as the presence of karyotypically distinct cell lines within an embryo and can be detected with Next Generation Sequencing (NGS) at a rate between 20-80%. High incidence of mosaicism has been reported in preimplantation embryos, with the blastocyst mosaicism being between 4-24% (Harton et al., 2017). Although mosaic embryos have a chance to implant (Munne et al., 2017; Spinella et al., 2018), their pregnancy rate is lower, with an increased miscarriage rate, possible risk of intrauterine growth retardation and uniparental disomy. Therefore, low-level mosaics are preferentially selected for transfer if no euploid embryos are found. Material and Methods: This retrospective study was based on 1958 preimplantation genetic testing for aneuploidy (PGT-A) cycles initiated between January 2017 and December 2018 in Istanbul Memorial Hospital. At least one euploid embryo was found for 1066 cycles (54.4%) and in 892 PGT-A cycles either full aneuploid or euploid/ mosaic embryos were diagnosed. PGT-A was done by NGS ReproSeq on Ion Torrent S5 (Thermo Fisher Scientific) following trophectoderm biopsy. Among 168 cycles at least one mosaic embryo was found, and 37 mosaic embryo transfer cycles were achieved (mean female age: 36.0). 42 patients refused the transfer of mosaic embryos and went through another PGT-A cycle (mean female age: 37.1). Student's t-test and Mann-Whitney U test were applied for continuous variables and Chi-square test for categorical group comparisons. Results: Among the 42 patients who have chosen to go for a second PGT-A cycle, 31 had at least one euploid embryo diagnosed (73.6%) and 28 couples came for a frozen-thawed embryo transfer cycle at the time the abstract was written. The mean mosaicism rate of the transferred embryos was 29% with a range of 20% to 40%. The biochemical pregnancy rate was 64.8% and 78.5% in the mosaic embryo transfer group and in the second PGT-A cycle group, respectively (p=0.23). The biochemical miscarriage rate was similar for both groups (16.7% vs. 13.6%, respectively). The clinical pregnancy rate was 54.1% and 67.9% for mosaic embryos and for the transfer of euploid embryos found in a second PGT-A cycle, respectively (p=0.26). The clinical miscarriage rate was 10% and 15.8% in the mosaic embryo transfer group and in the second PGT-A cycle group, respectively (p=0.71). The ongoing pregnancy rate was 48.6% and 57.1% for mosaics and second cycle's euploids, respectively (p=0.50). Conclusions: As no statistically significant differences were found and considering the high rate of at least one euploid embryo in the second PGT-A cycle (73.6%), couples should be encouraged to start a new PGT-A cycle. For advanced maternal age patients (≥42) and/ or patients with a diminished ovarian reserve a second PGT-A cycle may not be a realistic option, thus mosaic embryo transfers may still be feasible. The limitations of our study include the fact that this was a retrospective analysis. Cohort sizes are undeniably small which prevents us to obtain statistically significant results and draw strong conclusions. Prospective studies are warranted.